Coagulative (PAC) for iron removal in ferruginous water / Elias Mohd Den and Zadariana Jamil - Mohd Den, Elias; Jamil, Zadariana (2009)
The effect of PAC as a coagulant for the removal of iron in ferruginous raw water was investigated. The investigation involved an analysis of treatment through carrying out the flocculation and coagulation unit test in the determination of residual iron as well as the residual turbidity of the supernatants. The results show that the optimum iron removals were achieved at a pH of 5.2-8.0 PAC dosage of about 25 mg/l and with an almost 87% removal rate. The residual concentration iron in the treated water was O.12 mg/l, which is in compliance with the National/WHO permissible limit of 0.30 mg/l, whereas the residual turbidity was around 1. 17 NTU, well below the regulated limit of 5 NTU These investigative research data hopefully could provide some technical information for the possibility of full domestic applications to remove and reduce the undesirable excess iron from ferruginous groundwater sources with an insight that PAC is readily available and locally produced PAC is going to reduce the coagulant cost significantly.